2020
DOI: 10.2112/si95-009.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Decommissioning and Upgrading Urban Wastewater Treatment Plants on the Water Quality in a Shellfish Farming Coastal Lagoon (Ria Formosa, South Portugal)

Abstract: Impacts of decommissioning and upgrading urban wastewater treatment plants on the water quality in a shellfish farming coastal lagoon (Ria Formosa, South Portugal).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…2). Relatively similar spatial patterns for salinity, nutrients, faecal indicators, Chl-a, and chlorophytes were recently reported for other main WWTP (Faro-Olhão) discharging effluents into a relatively confined RF location (Jacob et al, 2020). However, the effects associated with this WWTP were more intense, affecting areas furthest from the discharge point (up to 750 m), probably due to a 3.5-fold higher effluent discharge rate, in respect with FNW (Jacob et al, 2020).…”
Section: Wastewater Footprints At Contrasting Ria Formosa Lagoon Areassupporting
confidence: 78%
See 1 more Smart Citation
“…2). Relatively similar spatial patterns for salinity, nutrients, faecal indicators, Chl-a, and chlorophytes were recently reported for other main WWTP (Faro-Olhão) discharging effluents into a relatively confined RF location (Jacob et al, 2020). However, the effects associated with this WWTP were more intense, affecting areas furthest from the discharge point (up to 750 m), probably due to a 3.5-fold higher effluent discharge rate, in respect with FNW (Jacob et al, 2020).…”
Section: Wastewater Footprints At Contrasting Ria Formosa Lagoon Areassupporting
confidence: 78%
“…These discharges represent a relevant nutrient source (Malta et al, 2017), and have impaired water quality (Bebianno, 1995;Newton et al, 2003;Cravo et al, 2015) and bivalve microbiological quality in specific areas of this lagoon (Martins et al, 2006;Almeida and Soares, 2012;Botelho et al, 2015;Cravo et al, 2015). More recently, some WWTPs discharging into the RF have upgraded their treatment technologies (Cravo et al, 2018), but the impact of these alterations was not yet fully assessed (see Jacob et al, 2020). This information is crucial for improving wastewater management strategies (e.g., Biancani et al, 2012;Machado and Imberger, 2012), promoting the condition of shellfish farming grounds, that intrinsically depend on water quality.…”
Section: Introductionmentioning
confidence: 99%
“…1.5 km from the Tavira inlet. The three stations used in our study were selected based on previous studies in Ria Formosa, which reported the WWTP influence up to 750 m from the discharge points, followed by reference lagoon conditions for the furthest stations [30,47,56]. The distance between stations increased from those closer to the discharge point (500 m, ALM 250-ALM 750) to the outer stations (1000 m, ALM 750-ALM 1750) due to the occurrence of stronger water quality gradients in areas closer to the WWTP discharge points [30,47,56].…”
Section: Sampling Strategymentioning
confidence: 99%
“…However, RF is exposed to various anthropogenic stressors [45,46], including discharges from wastewater treatment plants [30,47,48], and is located in an area particularly vulnerable to climate change [49]. Previous studies of phytoplankton in the RF lagoon, focusing on the western sector of the lagoon, have addressed the spatial-temporal dynamics of chlorophyll-a (e.g., [42,50,51]), assemblage structure [30,[52][53][54][55][56], production [57,58], specific HAB-forming taxa [59][60][61], and the effects of physico-chemical variables (temperature, light, CO 2 , nutrients, ultraviolet radiation) on phytoplankton growth and composition (e.g., [62][63][64][65][66][67]). However, no information on phytoplankton is currently available for the eastern sector of the lagoon, which is more affected by freshwater discharges [47] and where water quality is worst [46,51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation